Pengembangan Media Pembelajaran (Komik) Matematika Berbasis Karakter Kebangsaan - Septi Armi; Adisel Adisel; Poni Saltifa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to examine how the development of National Character-Based Mathematical Learning Media (Comics). This research is a development study using plomp model consisting of 3 stages namely: Initial investigation, Prototype Manufacturing and product assessment. The development test was conducted to a small group of 5 students and 1 Maths Teacher. The results of the study obtained data from the validation of media experts obtained a score of 76% with a very valid category, validation of language experts obtained a score of 86.36% with very valid criteria and validation of material experts obtained a score of 82.23% with criteria also very valid then the media was corrected according to the advice of the validator. Product trials by conducting practicality tests by teachers obtained a score of 80.76% with a very practical category and practicality tests to a small group obtained results of 84.23% with very practical criteria. In conclusion, the learning media (Comics) of National Character-Based Mathematics that have been developed is practically feasible to be used in the learning process. Keywords: National Character, Mathematics Comics, Learning Media